Four-dimensional design and programming of shape-memory magnetic helical micromachines. (June 2022) - Zhao, Fu; Rong, Weibin; Li, Dongjie; Wang, Lefeng; Sun, Lining
Highlights: Shape-memory helical micromachines were fabricated using shape memory polymer fibers. Various shape changes were realized by thermo-mechanical treatments of fibers. Swimming helical micromachines can accelerate or change direction in response to stimuli. Shape-memory components can be used for fabricating multi-component micromachines. Abstract: Diversified complex tasks put forward higher requirements on shape transformation abilities of magnetic microrobots. Shape memory polymers (SMPs) with desirable properties are ideal options for the development of microrobots. However, programming shape transformations for such small SMP robotic structures is still difficult. Here, a parametric design and programming method is reported for shape-memory magnetic helical micromachines. Through twice mechanically winding and annealing of UV lithography-modified ribbon-like polylactic acid fibers, the customization of permanent and temporary shapes of shape-memory helical micromachines was realized. Expected recoveries of helical micromachines from temporary shapes to permanent shapes were exhibited in response to thermal stimuli, showing diversified shape changes in helix angle, taper angle, length, diameter, and even chirality. Helical micromachines demonstrated controlled locomotion ability under rotating magnetic fields. Through dynamic design and shape programming, acceleration and direction reversal of swimming helical micromachines can be activated by environmental stimuli. Moreover, programmable shape-memory micro-components can be used to fabricate complex multi-component micromachines. This study provided an approach to overcome the programming difficulty of SMP microrobots. The shape-memory magnetic helical micromachines with programmable shape transformations and locomotion ability have great potential in various applications. Graphical abstract: Image, graphical abstract